Pengaruh Pandemı Covıd-19 terhadap Penjualan Suplemen Kesehatan dı Apotek “X” Kota Tarakan - Asma Lanuddin; Sari Wijayanti; Irma Novrianti; Dhea Erwina Suwanty (Politeknik Kaltara, 2023)
The World Health Organization declared Coronavirus disease a pandemic in 2020. Two Indonesian citizens were confirmed to have Covid-19 when the virus was first detected. Panic buying in meeting daily needs is one of the impacts caused by Covid-19, especially health supplements such as vitamins or immunomodulators, due to a lack of understanding from the public. This study aims to determine the effect of Covid-19 on sales of health supplement products at the